The use of force against non state actors. A critique to the “unwilling or unable” doctrine (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2019)
The emergence of new forms of terrorism in international level, made necessary to rethink the system of collective security. The gravity of these kind of attacks executed by non-state entities, gave the opportunity to the State victims to justify the use of force against them, in accordance with the unwilling or unable theory. This theory consists on the reconsideration of various legal norms which supposed to be consolidated in the international legal system, such as the self-defense and the attribution of conduct to a State. The present article consists on the analysis of the reasons for the emergence of the above theory and of the debates that had originate on the international doctrine.
Keywords: of force; self–defense; terrorism; attribution of conduct to a State